2021
DOI: 10.3390/electronics10212611
|View full text |Cite
|
Sign up to set email alerts
|

Social Welfare Maximization of Competitive Congested Power Market Considering Wind Farm and Pumped Hydroelectric Storage System

Abstract: The utilization of wind energy sources with energy storage systems has been increased in the power sector to satisfy the consumer’s energy demand with minimum price. This paper presents the impact of a wind farm (WF) and pumped hydroelectric storage (PHS) system in the competitive electricity market under a congested transmission system. The PHS system is used to compensate for the deviation of WF generation in the real-time electricity market. To investigate the impact of the proposed method, initially, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Though in case it has been observed that the speed and the force of the air cannot be controlled by the developer as a result of this the developer finds it difficult to match a high-speed containing air and convert them into electrical energy as well. Due to this uncontrolling power of the air, the output generated after the conversion has also become out of control and out of expectation as well [7].…”
Section: Power Quality Issues Of Wind Farmsmentioning
confidence: 99%
“…Though in case it has been observed that the speed and the force of the air cannot be controlled by the developer as a result of this the developer finds it difficult to match a high-speed containing air and convert them into electrical energy as well. Due to this uncontrolling power of the air, the output generated after the conversion has also become out of control and out of expectation as well [7].…”
Section: Power Quality Issues Of Wind Farmsmentioning
confidence: 99%
“…In Basu et al (2022b), the cuckoo search algorithm (CSA) was proposed to effectively maximize SW through the optimal placement and sizing of TCSC devices. Dawn et al (2021) introduced the MFO algorithm to address the congested market-clearing power problem, integrating wind and pumped hydroelectric storage systems in a deregulated environment, showcasing improved SW post-integration. Mixed-integer programing (MIP) was introduced in Khaloie et al (2020) to optimize profit and minimize emissions in RES-integrated power systems within a deregulated power sector, accounting for uncertainties associated with electricity market prices and RESs output through scenario characterization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, the CSA technique for LFC of a multi-area power system is used in [38]. Firefly (FA) based optimization is studied in [39,40]. GWO techniquebased LFC is reported in [41].…”
Section: Related Workmentioning
confidence: 99%